Caminhos identitários e educação das relações étnico-raciais no quilombo Rampa/MA - ABREU, Larissa Silva (2022)
This work is qualitative research which aims to analyze how the processes of subjectivation and construction of racial-ethnic identities among teachers are related to the educational practices within Quilombola School Education in a facility located in Quilombo Rampa, Vargem Grande, Maranhão. The research follows a constructionist perspective on Social Psychology, as well as the action research method proposed by Boaventura Sousa Santos (2008). The fieldwork was developed with four female and three male self-declared black teachers at the local school in Rampa. The procedures for data construction consisted of a focus group, participant observation, a field journal and the application of a questionnaire. The data constructed in this research were analyzed through Foucauldian Discourse Analysis. The study showed that initial and further education are important instances for both political and critical thinking about race and ethnic relations, as well as for the construction of the teachers’ racial-ethnic identities. And that the school’s job, when in constant exchange with the local quilombola practices and knowledges, is an important mobilizer in the practices of producing and stating black and quilombola identities. As institutions which potentialize regimes of truth, schools are observed in this study as one of the places where it is possible to learn how to be black, quilombola and to act against racism. Thus, the Education of Race and Ethnic Relations happens in the intersection of identities and subjectivities of the subjects involved in the educational process, as a result of the continuous dynamics which merge historical, cultural, individual and psychosocial processes throughout the discourses produced and conveyed as the truth.